Perspektiven angehender Lehrkräfte auf Forschendes Lernen – eine qualitative Längsschnittstudie im Referendariat und Berufseinstieg - Homt, Martina; Bloh, Bea; Wehde, Janis (Zeitschrift für Bildungsforschung)
Das hochschuldidaktische Konzept des Forschenden Lernens gilt als zentrales Element der universitären Lehrkräftebildung in Deutschland und ist in fast allen Bundesländern Bestandteil des Praxissemesters. Damit einhergehende Erwartungen im Hinblick auf den Professionalisierungsprozess von Lehrkräften fokussieren insbesondere die Vermittlung einer forschenden Grundhaltung, die auf eine nicht-wissenschaftsferne Berufsausübung abzielt. Wir fassen die forschende Grundhaltung als Professionsüberzeugung, die aus einer kognitiven, affektiven und handlungsbezogenen Komponente besteht und untersuchen die Komponenten im Zusammenspiel sowie im Längsschnitt. Mittels teilstrukturierter Interviews mit 22 angehenden Lehrkräften im Referendariat und Berufseinstieg, die sich im Praxissemester mit Forschendem Lernen befasst haben, werden das Verständnis (kognitive Komponente) und die Bedeutsamkeit (affektive und handlungsbezogene Komponente) Forschenden Lernens in der jeweiligen Ausbildungs- bzw. Berufsphase erfragt. Die Daten werden inhaltsanalytisch sowie typenbildend ausgewertet, um das Verständnis und die Bedeutsamkeit in der jeweiligen Phase, längsschnittliche Entwicklungen sowie das Verhältnis von Verständnis und Bedeutsamkeit herauszuarbeiten. Die Befunde zeigen, dass die Verständnisse von Forschendem Lernen sowohl im Referendariat als auch im Berufseinstieg variieren. Zudem ist das Konzept – laut Schilderungen der Befragten – durchaus bedeutsam für ihre Lern- und Handlungspraxis, jedoch nicht für alle und in unterschiedlich ausgeprägter Form. Die Typenbildung verdeutlicht, dass die fehlende Bedeutsamkeit Forschenden Lernens mit Fehlkonzepten einhergeht und eine höhere Bedeutsamkeit erkennbar ist, wenn Adaptionsleistungen hinsichtlich des Konzepts vorgenommen werden. Insgesamt ist im Sinne der Auffassung als Professionsüberzeugung die Anbahnung einer forschenden Grundhaltung bei einigen Befragten erkennbar. Implikationen für eine künftige Hochschulbildung ergeben sich u. a. mit Blick auf die Unterstützung von Studierenden bei Adaptionsleistungen für die (jeweilige) Praxis.

Wie kommt der „grüne“ Strom in die Steckdose? – Eine multidimensionale Analyse der Vorstellungen von Grundschulkindern zu nachhaltiger Energienutzung - Kirsch, Alexander; Hellmich, Frank; Blumberg, Eva; Puppe, Ricardo (Vorstellungen von Kindern zu Themenfeldern der Nachhaltigkeit)

„I matter!?“ – Eine Studie zur Vorbildfunktion von Lehrkräften im inklusiven Klassenzimmer. Vortrag auf der 90. Sektionstagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) in der DGfE. Thema: „Wissen|schaf[f]t|Ordnung? Zur Dynamik von Wissensordnungen in erziehungswissenschaftlicher Forschung, Gesellschaft und Pädagogik“. (angenommen) - Letzel-Alt, V; Hassani, S; Löper, Marwin Felix; Hellmich, Frank

Sozial-emotionale Kompetenzen und kooperatives Lernen im diversitätssensiblen Mathematikunterricht. Posterpräsentation auf der 90. Sektionstagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) in der DGfE. Thema: „Wissen|schaf[f]t|Ordnung? Zur Dynamik von Wissensordnungen in erziehungswissenschaftlicher Forschung, Gesellschaft und Pädagogik“. (angenommen) - Casamassima, Gianna; Funk, Michael; Knickenberg, Margarita; Löper, Marwin Felix; Hellmich, Frank; Grosche, M; Zimmer, L; Grüßing, M; Weß, N

Lehrkräfteperspektiven auf die Förderung sozial-emotionalen Lernens in der Grundschule. Posterpräsentation auf der 90. Sektionstagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) in der DGfE. Thema: „Wissen|schaf[f]t|Ordnung? Zur Dynamik von Wissensordnungen in erziehungswissenschaftlicher Forschung, Gesellschaft und Pädagogik“. (angenommen) - Funk, Michael; Hellmich, Frank

Merkmale guter inklusiver Schulen – Zusammenhänge auf Lehrkraft-Ebene - Wohnhas, Verena; Böhm-Kasper, Oliver; Neumann, Phillip (PraxisForschungLehrer*innenBildung. Zeitschrift für Schul- und Professionsentwicklung)
Der Beitrag beschäftigt sich mit der Frage, ob die Merkmale guter inklusiver Schulen – verstanden als Schulentwicklungsinstrument – mit der Arbeitszufriedenheit und den Selbstwirksamkeitsüberzeugungen von Lehrkräften in inklusiven Gesamt- und Sekundarschulen zusammenhängen. Dazu werden Daten aus dem BMBF-geförderten Projekt BiFoKi (Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen) von N = 119 Lehrkräften analysiert. Die Ergebnisse zeigen, dass die Merkmale guter inklusiver Schulen einen großen Teil der Varianz in der Arbeitszufriedenheit aufklären. Die kollektive Selbstwirksamkeitsüberzeugung korreliert stark mit den Merk-malen guter inklusiver Schulen und der Arbeitszufriedenheit der Lehrkräfte. Für die individuelle inklusionsbezogene Selbstwirksamkeitsüberzeugung zeigen sich itemspezifische Befunde, die diskutiert werden. Implikationen für die schulische Praxis werden abgeleitet.
Keywords: Arbeitszufriedenheit; Inklusion; Merkmale guter inklusiver Schulen; Selbstwirksamkeit; kollektive Selbstwirksamkeitsüberzeugung

Parental (dis)satisfaction with school placement to achieve inclusion: a cross-country comparison - Johansson, Veslemøy Maria Fossum; Gibson, Suanne; Woodcock, Stuart; Dechsling, Anders; Kullmann, Harry; Herrebrøden, Marte Karoline; Ulriksen, Line Britt; Nordahl-Hansen, Anders (Frontiers in Education)
Background – This study draws on data from a larger international project exploring parents' perceptions of the education of their children with special educational needs and/or disabilities (SEND). Using responses from 1, 309 parents in Australia, England, Germany, and Norway it examines parental satisfaction with mainstream and special schools, and parents' school placement preferences, including willingness to change schools. Parental satisfaction is assessed as an overall evaluation of how well the child's school placement meets their needs, without distinguishing between specific aspects of the school experience. The study also explores whether the child's level of support is associated with these perceptions. Based on a human rights perspective, we highlight parents’ perspectives and their role in the development of more inclusive education systems, without promoting one model of schooling over another. Methods – Responses from 1, 309 parents across four countries were analysed using descriptive and inferential statistics. Non-parametric tests compared satisfaction across school types, chi-squared tests assessed associations with willingness to change schools, and binary logistic regression examined whether level of support was associated with parents' willingness to change school placement. Results – Parents in England, Germany, and Norway reported higher satisfaction with special schools than with mainstream schools. No statistically significant difference was observed in Australia. Parents of children in special schools were less likely to report considering changing schools, particularly in England and Norway. Higher pupil support needs were significantly associated with parents’ willingness to change school across the combined sample. These findings suggest that parental satisfaction with their child's education and their preferences regarding school placement may be shaped by both school type and how well pupils' support needs are perceived to be met. Discussion and conclusion – The role of parents as key stakeholders in developing inclusive education systems, consistent with the Convention on the Rights of Persons with Disabilities (CRPD) is emphasised. While parents in special schools in three of the four countries reported higher satisfaction, the reasons for this remain unclear. Understanding the factors shaping parental satisfaction is essential for developing inclusive and responsive learning environments. These findings offer a starting point for future research on how education systems can better align policy commitments with families’ lived experiences.
Keywords: human rights; inclusion; inclusive education; international study; parents; school development; special educational needs

Praxisforschung in Schule und Unterricht

Bildungstechnologie in der schulischen Bildung - Herzig, Bardo (The Age of EdTech: Bildungstechnologie im Spannungsfeld zwischen Innovation und Qualität)

Reframing school leadership for the digital age - Cochrane, Janet; Tan, Seng Chee; Phillips, Michael; Eickelmann, Birgit; Kral, Marijke; Chammon, Jacob; Pangeni, Shesha Kanta (Computers and Education Open)

The role of social-emotional competencies for children’s cooperative learning processes in inclusive primary school classrooms. Individual Oral Presentation. 5th Porto International Conference on Research in Education (ICRE) 2026. - Hellmich, Frank; Knickenberg, Margarita; Funk, Michael; Casamassima, Gianna; Löper, Marwin Felix

Predictors of primary school students’ prosocial behaviour toward peers with social-emotional difficulties in inclusive education: Insights from the Theory of Planned Behaviour. Individual Oral Presentation. 5th Porto International Conference on Research in Education (ICRE) 2026. - Löper, Marwin Felix; Hellmich, Frank

Predictors of primary school students’ prosocial behaviour toward peers with social-emotional difficulties in inclusive education: Insights from the Theory of Planned Behaviour. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. - Löper, Marwin Felix; Knickenberg, Margarita; Hellmich, Frank

Teachers’ conceptualizations of social-emotional competencies in cooperative learning: Insights from inclusive primary school classrooms. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. - Knickenberg, Margarita; Funk, Michael; Casamassima, Gianna; Löper, Marwin Felix; Hellmich, Frank

Social and emotional competencies for cooperative learning in inclusive primary education: A project overview. Poster Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. - Casamassima, Gianna; Funk, Michael; Knickenberg, Margarita; Löper, Marwin Felix; Grosche, M.; Zimmer, L.; Grüßing, M.; Wess, N.; Hellmich, Frank

‘School is no longer a lone wolf effort’: leadership strategies for inclusive, community-based school cultures - Woodcock, Stuart; Avramidis, Elias; Sharma, Umesh; Subban, Pearl; Sahli Lozano, Caroline; Kullmann, Harry; Loreman, Tim; Wüthrich, Sergej; Knickenberg, Margarita (School Leadership & Management)
Based on the premise that the successful implementation of inclusion is largely dependent on the educators’ commitment to inclusive ideals, this study sought to examine the ways principals promote an inclusive vision and foster the development of associated practices in their school community. The study employed an exploratory qualitative research design, collecting data through semi-structured interviews and focus groups with 12 principals of highly-ranked inclusive schools from four countries: Australia, Italy, Switzerland, and Spain. In so doing, the emphasis was placed on the principals’ perspectives and practices that contribute to the development of an inclusive school culture. The iterative process of thematic analysis revealed five broad key factors that affect and impact school inclusivity, namely: institutional commitment to a collective inclusive culture; family partnership and co-responsibility; collaboration among key stakeholders (e.g. students, teachers, other staff); students’ voice and agency; and building and sustaining inter-institutional partnerships. This paper concludes by advocating a community-based approach model to school inclusion by identifying key factors on which principals can rely to navigate material, social, and political challenges.
Keywords: Inklusive Bildung; Schulentwicklung; Schulleitung; Gemeinschaftlichkeit; Haltung

Determinanten der politischen Involviertheit von Lehramtsstudierenden und damit verbundene Implikationen für die Lehrer*innenbildung - Wehde, Janis

Feedback und selbstbezogene Kognitionen als Prädiktoren für die Mathematikleistungen von Grundschulkindern. Vortrag im Rahmen des Symposiums „Lernen durch Feedback von Lehrpersonen, Eltern und Schüler:innen“ (Sebastian Röhl & Fabian Hoya) auf der 12. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung als Schlüssel für gesellschaftliche Herausforderungen: Interdisziplinäre Beiträge aus der Bildungsforschung“ - Löper, Marwin Felix; Finke, Nils; Knickenberg, Margarita; Hellmich, Frank

Examining aspects of students’ current academic motivation in relation to peer interactions and social environment in the classroom using the Experience sampling method - Knickenberg, Margarita; Zurbriggen, Carmen

Exploring the role of individual and collective efficacy beliefs and attitudes in teachers’ intentions to implement inclusive practices: Evidence from Canada, Germany and Switzerland - Knickenberg, Margarita; Kullmann, Harry